Workshop Klein- und Mittelunternehmen in Japan V - Themenschwerpunkt: M&A in Japan - ein neues Instrument der Unternehmenspolitik? - Karl Lichtblau; Werner Pascha; Cornelia Storz (Gerhard-Mercator-Universität Duisburg, Institut für Ostasienwissenschaften, 2000)
The volume is a collection of papers on 'M&A in Japan - a new instrument for corporate policy', with a special emphasis on small and medium firms, presented at a workshop in December 1999. The first contribution gives an overview of international M&A in recent years. Next, preliminery results of a survey among German enterprises with business interests in Japan are discussed. The third paper concentrates on the consequences ofthe current M&A boom on the Japanese enterprise system and on corporate govemance. Finally, legal options and other implementation issues faced by foreign investors undertaking M&A in Japan are discussed.
Keywords: 330; Klein- und Mittelunternehmen (KMU); Mittelstand; mergers & acquisitions (M&A); Fusionen; Risikokapital; Japan; Deutschland; Übernahme; Klein- und Mittelunternehmen; Corporate Governance; Deutsch; Japan